ANALISIS PENGARUH LINGKUNGAN KERJA, GAYA KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN - Ayu Fadlilah, Elvira Nur; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2020)
In this era of global competition, companies are required to be able to compete, so companies must have good perfomance. One component of creating a company perfomance in order to compete is superior human resource perfomance. One factor that can affect perfomance is job satisfaction. Job satisfaction can be influenced by the work environment, leadership style, and the organizational culture of company. So the purpose of this tudy is to find out and analyze the influence of the work environment, leadership style, and organizational culture on employee perfomance through employee job satsisfaction.This research uses quantitative methods by distributing questionnaires to get respondent data. The population of this study was blue-collar workers in the food industry sector wich amounted to 157 employee. The sample used amounted to 100 employees of CV. Virgin Cake and Bakery Ungaran branch. Data analysis techniques in this study used Partial Least Square with SmartPLS 3.0 software to determine the path efficiency and the effect of independent variables on the dependent variables.Â The result show that the work environment has a positive but not significant effect on employee job satisfaction and employee perfomance. Leadership style has a positive but not significant effect on employee perfomance. On the other hand, leadership style and organizational culture have a positif and significant effect on employee job satisfaction. In addition, organizational culture and employee job satisfaction have a positive and significant effect on employee perfomance.